Enhanced energy storage performance in Ag(Nb,Ta)O3 films via interface engineering - Xiao Zhai; Jun Ouyang; Weijie Kuai; Yinxiu Xue; Kun Wang; Nengneng Luo; Hongbo Cheng; Hanfei Zhu; Chao Liu; Limei Zheng (Journal of Materiomics)
Dielectric capacitors with ultrahigh power density and ultra-fast charge/discharge rate are highly desired in pulse power fields. Environmental-friendly AgNbO3 family have been actively studied for its large polarization and antiferroelectric nature, which greatly boost the electric energy storage performance. However, high-quality AgNbO3-based films are difficult to fabricate, leading to a low breakdown field Eb (<1.2 MV/cm) and consequently arising inferior energy storage performance. In this work, we propose an interface engineering strategy to mitigate the breakdown field issue. A Ag(Nb,Ta)O3/BaTiO3 bilayer film is proposed, where the BaTiO3 layer acts as a p-type semiconductor while Ag(Nb,Ta)O3 layer is n-type, together with the n-type LaNiO3 buffer layer on the substrate, forming an n-p-n heterostructure. The n-p-n heterostructure elevates the potential barriers for charge transport, greatly reducing the leakage current. An extremely large breakdown field Eb∼4.3 MV/cm is achieved, being the highest value up to date in the niobate system. A high recoverable energy density Wrec∼62.3 J/cm3 and a decent efficiency η∼72.3% are obtained, much superior to that of the Ag(Nb,Ta)O3 monolayer film (Wrec∼46.4 J/cm3 and η∼80.3% at Eb∼3.3 MV/cm). Our results indicate that interface engineering is an effective method to boost energy storage performance of dielectric film capacitors.